Beauty and Aesthetics in the Contemporary Mind - Yeon, Madison (Journal of Student Research, 2022)
Abstract The concept of beauty and taste is one that has been grappled with for centuries throughout history as different ages, ethnicities, and time periods all define their own idea of what is beautiful. Traditionally counted as an ultimate value, alongside goodness, truth, and justice (Sartwell), the nature of beauty is a primary theme in every culture that is as relevant in today’s modern world just as it was in 500 BC. Philosophies of beauty and aesthetics look into the meaning, perception, and nature of beauty and what properties make something more beautiful than others, if such properties exist at all. In this study, three major philosophical theories of aesthetics (classical, modern, and Kantian) were analysed and categorised as objective or subjective viewpoints. Using an experimental philosophy approach and the concept of nominalism, realism, and anti-realism, participants were surveyed to see if they leaned more towards an objective or subjective viewpoint in order to determine which historical aesthetic philosophy influences the contemporary mind the most. The results of this study indicated that the contemporary mind leaned more towards a classical conception of beauty and aesthetics, showing that there may be an objective standard of beauty within modern society closely related to properties such as symmetry and proportion.